Trichomes- their uses to the plant - Thackrey, Harriet Emerson (My University, 1898)
Introduction: The study of trichomes is very interesting, because of the great diversity inform and function, while at the same time there is a similarity between all of the forms. They are commonly called plant hairs, because of the hair like coating of some leaves. They are also known under several other names, as sprines, prickles, briers, and dour which are all more or less descriptive terms. Some of these forms are often confused with other parts of the plant which are modified into forms similar to trichomes. The thorns on the honey locust and osage orange are really modified stems but they look very much like the spines on the goose berry and wild rose. The only way to distinguish is to determine whether or not they originate in the epidermis. If they do they are truly trichomes, if not they belong under some other classification.
Citation: Thackrey, Harriet Emerson. Trichomes- their uses to the plant. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Trichomes; Diversity; Plant; Theses; Manuscripts (documents)